Analisis Implementasi Undang-Undang Wakaf Nomor 41 Tahun 2004 Terhadap Peran Nazhir dalam Pengelolaan Wakaf: Studi Kasus Putusan Perkara Nomor 20/Pdt.G/2023/PN Msb - Nuridin, Nuridin; Hidayat, Yusup (UNES Law Review, 2024)
This research analyzes the application of the Waqf Law Number 41 of 2004 to the role of nazhir in waqf administration, taking the case study of Case Decision Number 20/Pdt.G/2023/PN Msb as a basis. The focus is on evaluating the role and performance of the nazhir in the legal context, as well as its impact on the continuity of the waqf and the integrity of the nazhir. Through a normative legal approach, this research identifies the nazir's responsibilities and duties in maintaining and managing waqf assets following Sharia principles. Analysis of Decision Number 20/Pdt.G/2023/PN Msb reveals the judge's consideration of the nazir's role in managing waqf land, especially in the context of the conflict over ownership of land intended for the Baitul Makmur Mosque. This research explores the relationship between the nazhir's role and the implementation of the Waqf Law, as well as the impact of the judge's considerations on the decision in the case. As a result, protection of waqf ownership, especially in the context of waqf land, emerged as crucial. Emphasis is also placed on the important role of nazhir in safeguarding and managing religious assets for the public interest.